Sources of individual differences in adults’ ICT skills : a large-scale empirical test of a new guiding framework - Wicht, Alexandra [Verfasser]; Reder, Stephen [Verfasser]; Lechner, Clemens M. [Verfasser] (My University, 2021)
"We develop an integrative conceptual framework that seeks to explain individual differences in the ability to use information and communication technologies (ICT skills). Building on practice engagement theory, this framework views the continued usage of digital technolo gies at work and in everyday life (ICT use) as the key prerequisite for the acquisition of ICT skills. At the same time, the framework highlights that ICT use is itself contingent upon individual and contextual preconditions. We apply this framework to data from two recent German large-scale studies (N = 2,495 and N = 2,786, respectively) that offer objective measures of adults’ ICT skills. Findings support our framework’s view of ICT use as a key prerequisite for ICT skills. Moreover, they demonstrate that literacy skills have strong asso ciations with ICT skills, largely by virtue of their indirect associations through ICT use. By comparison, regional digital cultures (as proxied by internet domain registration rates) evince only limited explanatory power for individual differences in ICT skills." (Author's abstract ; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.2.2 Internet / Mediengesellschaft; P 1.2 Erwachsene; 370; 300; Informationstechnik; Digitalkompetenz; Mediennutzung; Lesekompetenz; Schreibkompetenz; Erwachsener; Nationales Bildungspanel